Biomechanical Comparison of Onlay Distal Biceps Tendon Repair: All-Suture Anchors Versus Titanium Suture Anchors. Issue 10 (August 2019) - Otto, Alexander; Mehl, Julian; Obopilwe, Elifho; Cote, Mark; Lacheta, Lucca; Scheiderer, Bastian; Imhoff, Andreas B.; Mazzocca, Augustus D.; Siebenlist, Sebastian
Background: A rupture of the distal biceps tendon is the most common tendon rupture of the elbow and has received increased attention in the past few years. Newly developed all-suture anchors have the potential to minimize surgical trauma and the risk of adverse events because of the use of flexible drills and smaller drill diameters. Purpose/Hypothesis: The purpose was to biomechanically compare all-suture anchors and titanium suture anchors for distal biceps tendon repair in cadaveric specimens. The hypothesis was that all-suture anchors would show no differences in load to failure or displacement under cyclic loading compared with titanium suture anchors. Study Design: Controlled laboratory study. Methods: Sixteen unpaired, fresh-frozen human cadaveric elbows were randomized to 2 groups, which underwent onlay distal biceps tendon repair with 2 anchors. Bone mineral density at the radial tuberosity was evaluated in each specimen. In the first group, distal biceps tendon repair was performed using all-suture anchors. In the second group, titanium suture anchors were applied. After cyclic loading for 3000 cycles, the repair constructs were loaded to failure. The peak load to failure as well as repair construct stiffness and mode of failure were determined. Results: The mean (±SD) peak load was 293.53 ± 122.15 N for all-suture anchors and 280.02 ± 69.34 N for titanium suture anchors ( P = .834); mean stiffness was 19.78 ± 2.95 N/mm and 19.30 ± 4.98 N/mm, respectively ( P = .834). The mode of failure was anchor pullout for all specimens during load to failure. At the proximal position, all-suture anchors showed a displacement of 1.53 ± 0.80 mm, and titanium suture anchors showed a displacement of 0.81 ± 0.50 mm ( P = .021) under cyclic loading. At the distal position, a displacement of 1.86 ± 1.04 mm for all-suture anchors and 1.53 ± 1.15 mm for titanium suture anchors was measured ( P = .345). A positive correlation between bone mineral density and load to failure was observed ( r = 0.605; P = .013). Conclusion: All-suture anchors were biomechanically equivalent at time zero to titanium suture anchors for onlay distal biceps tendon repair. While the proximally placed all-suture anchors demonstrated greater displacement than titanium suture anchors, the comparable displacement at the distal position as well as the similar load and mechanism of failure make this difference unlikely to be clinically significant. Clinical Relevance: All-suture anchors performed similarly to titanium suture anchors for onlay distal biceps tendon repair at time zero and represent a reasonable alternative.